The neonatal intubation causes defects in primary teeth of premature infants - de Oliveira Melo, Norma Suely Falcao; da Silva, Regina Paula Guimaraes Vieira Cavalcante; de Lima, Antonio Adilson Soares (Biomedical papers, 2014)
Aim: This study aimed to evaluate the relationship between intubation during the neonatal period and enamel defects in primary teeth of preterm infants. It was an observational, prospective, analytical and sampling of convenience. We selected 157 children who had average birth weight of 1656.3 ± 627.8 g, gestational age of 31.7 ± 2.7 weeks and the examination of chronological age 2.2 ± 0.6 years old.Methods: Clinical examination of the oral cavity showed that the frequency of enamel defects was higher (86.3%) among children intubated when compared to non-intubated children (13.7%). The enamel defects was found to be inversely proportional to gestational age. The intubation time was related to the probability of occurrence of DDE (P<0.001), in other words, the greater the number of days intubated, the greater the chance of DDE. In children intubated, hypoplasia mainly affected the upper teeth on the left side of the mouth.Conclusion: Tracheal intubation in the neonatal period is the main cause of enamel defects in primary teeth of children born preterm. The longer the duration of intubation, the greater the chance of developing dental enamel defect. The area of action during movement of the laryngoscope toggle corresponds to the region most affected by tooth enamel hypoplasia in children intubated, upper right central incisor, lateral incisor and upper left.
Keywords: prematurity; tracheal intubation; enamel defects